Geography and Sentencing: Does Country of Citizenship Influence Sentence Longevity? - Iles, Gale; Adegun, Oladipupo V. (International Journal of Criminology and Sociology, 2018)
Contentious debates on immigrants in the United States has led to growing interest in their treatment in the criminal justice system. Much of what is known, however, springs from research that treats immigrants as a homogeneous group. The lumping of all immigrants into one category potentially mask variances in sentencing based on national origins. The current study disaggregates federal sentencing data to explore whether length of sentence differs by the defendants’ geographical region of citizenship. After controlling for a number of legal and extra-legal factors, sentences imposed upon Mexican citizens were found to be longer than sentences meted out to defendants who are citizens of other countries. Evidence suggesting that national origin has a stronger influence on sentence length than race/ethnicity and legal status was also detected. Implications of the findings and directions for future research are discussed.